Forecasting Analysis of Electricity Consumption in East Kolaka and Konawe Districts Using Prophet Method (Jurnal Matematika, Statistika dan Komputasi, 2025)
This study aims to determine electricity consumption forecasting in East Kolaka Regency and Konawe Regency using the Prophet method. The data used in this study are secondary data obtained from PT PLN ULP Unaaha which consists of data on the amount of monthly electricity consumption from January 2019 to November 2023. The results showed that the Prophet method obtained an error calculation value using MAPE of 1.09%. So that the Prophet method can be used to forecast electricity consumption in East Kolaka Regency and Konawe Regency.
Keywords: Forecasting; Prophet; Electricity; consumption; MAPE; MSE